2018
DOI: 10.1093/jas/sky328
|View full text |Cite
|
Sign up to set email alerts
|

Ergot alkaloids induce vasoconstriction of bovine uterine and ovarian blood vessels

Abstract: Fescue toxicosis is a syndrome that impairs growth and reproduction in cattle grazing endophyte-infected tall fescue [Lolium arundinaceum [(Schreb.].) Darbysh)] in the United States, resulting in approximately $1 billion in annual economic loss in species that utilize this forage resource. Approximately 90% of tall fescue contains an endophytic fungus (Epichloë coenophiala) that produces ergot alkaloids. Ergot alkaloids cause vasoconstriction and reduced blood flow to the extremities; however, it remains unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Additionally, ergot alkaloids have been known to cause contractile responses in a variety of vessels and species such as the lateral saphenous veins in cattle, the distal palmar artery of horses, the carotid and auricular arteries in goats, tail arteries in rats, and iliac arteries of guinea pigs (Schoning et al, 2001;Klot et al, 2007;McDowell et al, 2013;Aiken and Flythe, 2014). It was also documented that heifers exposed to E+ fescue exhibited reductions in the uterine vein and artery (and ovarian vein and artery) during the later stages of the estrous cycle (Poole et al, 2018). This further supported the conclusion made by Dyer (1993) that ergovaline, specifically, is a potent vasoconstrictor in the bovine umbilical and uterine arteries and has the potential to directly impair blood flow to the uterus and developing placenta during gestation.…”
Section: Placental Measuresmentioning
confidence: 99%
“…Additionally, ergot alkaloids have been known to cause contractile responses in a variety of vessels and species such as the lateral saphenous veins in cattle, the distal palmar artery of horses, the carotid and auricular arteries in goats, tail arteries in rats, and iliac arteries of guinea pigs (Schoning et al, 2001;Klot et al, 2007;McDowell et al, 2013;Aiken and Flythe, 2014). It was also documented that heifers exposed to E+ fescue exhibited reductions in the uterine vein and artery (and ovarian vein and artery) during the later stages of the estrous cycle (Poole et al, 2018). This further supported the conclusion made by Dyer (1993) that ergovaline, specifically, is a potent vasoconstrictor in the bovine umbilical and uterine arteries and has the potential to directly impair blood flow to the uterus and developing placenta during gestation.…”
Section: Placental Measuresmentioning
confidence: 99%
“…Similarly, ergot alkaloids have a high affinity towards α 2 -adrenergic receptors [47,48]. Additionally, a couple of studies have used Doppler ultrasonography to show that heifers chronically exposed to endophyte-infected tall fescue have reduced caudal artery area and blood flow to the peripheral arteries when compared to heifers consuming endophyte-free tall fescue [49,50], however literature describing the extent to which vasoconstriction occurs to the internal organs is limited [16].…”
Section: Ergot Alkaloids and Ovarian Functionmentioning
confidence: 99%
“…Reduced blood to the periphery might cause hypoxemia resulting in subsequent increase in respiration rates, which is a known symptom in cattle experiencing FT [54]. In humans, Vecchione et al [52] found that BPIFB4 is a powerful enhancer for endothelial vasorelaxation and revascularization, further supporting its potential role in FT. WNT11 has several functions, such as promotion of cardiomyocyte differentiation, activation of kinase activity, and osteoblast maturation [55].…”
Section: Most Differentially Expressed Genes On Week 5 At Uprsmentioning
confidence: 99%